Barriers to high-tech SME internationalization: Finnish health-tech companies entering Saudi Arabian market - Rantanen, Laura (My University, 2020)
Across the world, healthcare sector is growing due to reasons such as aging populations and growing middle class. At the same time, new technological innovations are changing healthcare, making health-tech a rapidly growing industry. Finland has a great reputation as a country for producing good quality healthcare products, and in fact, over 80% of Finnish health-tech products end up being exported. Saudi Arabia is a growing market for health-tech companies as the market is investing constantly more to healthcare because of growing population size and increasing amount of lifestyle diseases. Finland and Saudi Arabia have already begun establishing cooperation in healthcare sector. However, as Finland and Saudi Arabia are markets distant to each other, both geographically and culturally, there are some challenges the Finnish health-tech companies internationalizing to Saudi Arabia may encounter. The objective of the study was to find out what are the main barriers Finnish health-tech companies encounter when entering the Saudi Arabian market. More closely, the study aimed to find out what are the internal barriers and external barriers the companies encounter during the internationalization process. The study was performed as a qualitative research, collecting data by interviewing managers from three Finnish health-tech SMEs, all of which have currently ongoing business operations in the Saudi Arabian market. The results suggested that the main internal barriers are related to finding the right partner in Saudi Arabia, lack of human resources and lack of relevant knowledge of the Saudi Arabian business culture and regulations. Main external barriers were found to be related to the difficult host-country economic and sociocultural environments as well as to the complex government regulations. Based on the findings, some recommendations were provided for managers of health-tech SMEs heading to the Saudi Arabian market. The recommendations include focusing on finding the right partner, investing time in acquiring knowledge on the Saudi Arabian culture and regulations, and focusing on applying secure payment methods. Finally, some suggestions for further research were made.

Terveydenhuoltoala on maailmalla jatkuvassa kasvussa suurenevan keskiluokan ja vanhenevan väestön vuoksi. Samaan aikaan terveydenhuolto on muutoksessa, kun teknologiset innovaatiot valtaavat alaa terveysteknologian muodossa. Terveysteknologia on Suomessa nopeimmin kasvava korkean teknologian vientiala. Jopa yli 80% suomalaisesta terveysteknologiasta viedään ulkomaille. Saudi-Arabia on nouseva terveysteknologian markkina-alue maan nopeasti kasvavan väestöluvun ja laajalti levinneiden elintapasairauksien vuoksi. Suomi ja Saudi-Arabia tekevät jo nyt yhteistyötä terveydenhuoltoalalla, mutta kasvupotentiaalia yhteistyölle löytyy vielä paljon. Maat ovat hyvin kaukana toisistaan, niin maantieteellisesti kuin kulttuurillisestikin, minkä takia suomalaiset terveysteknologiayritykset saattavat kohdata haasteita pyrkiessään Saudi-Arabian markkinoille. Tutkimuksen tavoitteena oli selvittää, mitkä ovat suurimmat haasteet, joita pienet ja keskisuuret suomalaiset terveysteknologiayritykset kohtaavat kansainvälistyessään Saudi-Arabian markkinoille. Tavoite jaettiin kahteen alatavoitteeseen, joista ensimmäisessä selvitettiin yrityksen sisäisistä toiminnoista kumpuavia haasteita, ja toisessa yrityksen ulkopuolisesta ympäristöstä johtuvia haasteita. Tutkimus suoritettiin laadullisena tutkimuksena kolmea suomalaista terveysteknologiayritystä haastatellen. Kaikilla haastateltavilla yrityksillä on tällä hetkellä liiketoimintaa Saudi-Arabiassa. Tutkimuksen tuloksista selvisi, että yritykset kohtasivat Saudi-Arabian markkinoille pyrkiessään sekä sisäisiä että ulkoisia haasteita. Suurimmat sisäiset haasteet olivat tiedonpuute Saudi-Arabian toimintaympäristöstä, yrityksen henkilöstövaje sekä sopivan paikallisen kumppanin löytäminen. Suurimmat ulkoiset haasteet taas liittyivät Saudi-Arabian taloudelliseen ja sosiokulttuuriseen ympäristöön sekä maan monimutkaisiin terveysteknologiaa koskeviin regulaatioihin. Tulosten pohjalta tehtiin käytännön suosituksia terveysteknologiayrityksille, jotka suunnittelevat Saudi-Arabian markkinoille menemistä. Suosituksia ovat esimerkiksi paikallisen kumppanin huolellinen valinta, Saudi-Arabian liiketoimintakulttuuriin ja regulaatioihin tutustumiseen panostaminen, sekä turvallisten ja luotettavien maksutapojen käyttö. Tutkimuksen pohjalta annettiin lopuksi ehdotuksia jatkotutkimukseen.